2009
DOI: 10.1017/s0317167100007812
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Attacks While Driving: Quality of Life in Persons with Epilepsy

Abstract: Objective:To study the effect on quality of life (QOL) of a seizure attack while driving in persons with epilepsy (PWE).Methods:From four provincial and eight university hospitals in Thailand, we enrolled epileptic patients who drove a car or motorcycle or used to drive. The SF-36 questionnaire was used to evaluate QOL. The mean SF-36 score for all dimensions was calculated and compared with patients who either had or did not have a seizure attack while driving and in those who either had or had not been invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…Merila za ugotavljanje telesne in duševne zmožnosti za kandidate za voznike in voznike prve skupine z epilepsijo v Republiki Sloveniji (prirejeno po 49 ).…”
Section: Tabelaunclassified
See 1 more Smart Citation
“…Merila za ugotavljanje telesne in duševne zmožnosti za kandidate za voznike in voznike prve skupine z epilepsijo v Republiki Sloveniji (prirejeno po 49 ).…”
Section: Tabelaunclassified
“…43 Problem prepovedi vožnje je zelo čustven predvsem za osebe z na novo diagnosticirano epilepsijo, pogosto pa tudi za njihove svojce.49 Osebe z epilepsijo, ki so prvič izvedele o omejitvah vožnje, so najpogosteje občutile žalost (57 %). 44 Raziskave kažejo, da približno ena tretjina oseb z nenadzorovanimi epileptičnimi napadi nadaljuje z vožnjo kljub prepovedi36,43,44,50 ter da se ne držijo omejitev vožnje v glavnem zaradi razlogov, povezanih z zaposlitvijo.14,16,33,36,43,44,50 Pomembni so rezultati ene od raziskav, ki so pokazali, da je med osebami z epilepsijo, ki so v zadnjem letu vozile avto, kar 77 % zaposlenih, medtem ko je bilo zaposlenih le 23 % tistih, ki niso vozile.50 Merilo, na podlagi katerega se osebe z epilepsijo odločajo za nadaljevanje Tabela 3: Merila za ugotavljanje telesne in duševne zmožnosti za kandidate za voznike in voznike druge skupine z epilepsijo v Republiki Sloveniji (prirejeno po 49 ).…”
Section: Obravnava Bolnika Z Epilepsijo V Ambulanti Družinskega Zdravunclassified
“…A Finnish study concluded that the accident rate was not increased among patients with epilepsy (n = 81) compared with control subjects (23). Fatal driver crashes because of seizures are rare events (16), and, according to questionnaire surveys, 26-28% of individuals with epilepsy report having had a car accident because of a seizure (24,25).…”
Section: Risk Of Traffic Accidentsmentioning
confidence: 99%
“…This also affects the economy and society with epileptics being unemployed more than normal people so patients' incomes are likely lower. They need to depend on family or other people because of their condition; these factors, of course, affect the quality of living standards of patients (10,11).…”
Section: Introductionmentioning
confidence: 99%